2017
DOI: 10.1002/ejic.201700559
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Microwave Synthesis of 2‐Fluoro‐diazaborolidines and Their Reaction with Lithium Phosphanides

Abstract: Condensation of N,N′‐disubstituted ethylenediamines with BF3·OEt2, in the presence or absence of an auxiliary base, gives mixtures of 2‐fluoro‐1,3,2‐diazaborolidines and ammonium tetrafluoroborates, respectively. Using BF3·NEt3 as the reactant allows the introduction of the boron source and the auxiliary in a single component, but suffers from the inhibition of the cyclisation by an excess of free amine formed as a by‐product. In contrast, rapid and quantitative consumption of the starting materials is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The reaction of 7 a with either 2 a or 8 a was performed in different chlorinated nondonor solvents (CH 2 Cl 2 , CD 2 Cl 2 , and CDCl 3 ) and at various temperatures (Scheme and Table ). In a typical experiment (e.g., entry 2 in Table ), compounds 7 a and 2 a were mixed in dichloromethane at ambient temperature to give a 1 m starting concentration of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 7 a with either 2 a or 8 a was performed in different chlorinated nondonor solvents (CH 2 Cl 2 , CD 2 Cl 2 , and CDCl 3 ) and at various temperatures (Scheme and Table ). In a typical experiment (e.g., entry 2 in Table ), compounds 7 a and 2 a were mixed in dichloromethane at ambient temperature to give a 1 m starting concentration of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we focused on monomeric phosphinoboranes, which are another type of ambiphilic P,B-based molecules. 30,31 A recent very comprehensive review 31 by Pringle et al classies these species containing a single P-B bond with a pyramidal P atom and the general formula R 2 P-BR 2 as borylphosphines 30,32,33 and those with a double P]B bond and trigonal planar P atom and the general formula R 2 P]BR 0 2 as phosphinoboranes. [34][35][36] Notably, we found that there are a limited number of reports on the reactivity of P-B bond systems towards small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The studies described in this work were performed using NHB‐phosphines carrying both CC‐unsaturated 1,3,2‐diazaborolyl substituents ( 5a – d , Scheme ) and CC‐saturated 1,3,2‐diazaborolidinyl substituents ( 6a , b ) on phosphorus. Ligands 5a – c and 6a , b had been reported previously and were synthesized as described. The P‐alkyl derivative 5d was newly prepared by analogy to 5a , b from the appropriate 2‐bromo‐1,3,2‐diazaborole and lithium dimethyl phosphide, and characterized by multinuclear NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The P‐alkyl derivative 5d was newly prepared by analogy to 5a , b from the appropriate 2‐bromo‐1,3,2‐diazaborole and lithium dimethyl phosphide, and characterized by multinuclear NMR spectroscopy. Like its congeners,, the new NHB‐phosphine is thermally stable in solution and the solid state, and can be shortly handled in air without decomposition.…”
Section: Resultsmentioning
confidence: 99%